The Roles of Traditional Chinese Medicine: Shen-Fu Injection on the Postresuscitation Care Bundle. (28th August 2013) - Zhang, Qian; Li, Chunsheng
Abstract : Survival rates following in-hospital and out-of-hospital cardiac arrests remain disappointingly low. Organ injury caused by ischemia and hypoxia during prolonged cardiac arrest is compounded by reperfusion injury that occurs when a spontaneous circulation is restored. A bundle of procedures, which may need to be administered simultaneously, is required. The procedures include prompt identification and treatment of the cause of cardiac arrest, as well as a definitive airway and ventilation together. Additional benefit is possible with appropriate forms of early goal-directed therapy and achieving therapeutic hypothermia within the first few hours, followed by gradual rewarming and ensuring glycaemic control to be within a range of 6 to 10 mmol/L. All these would be important and need to be continued for at least 24 hours. Previous studies have showed that the effects of Shen-Fu injection (SFI) are based on aconitine properties, supplemented by ginsenoside, which can scavenge free radicals, improve energy metabolism, inhibit inflammatory mediators, suppress cell apoptosis, and alleviate mitochondrial damage. SFI, like many other complex prescriptions of traditional Chinese medicine, was also found to be more effective than any of its ingredient used separately in vivo. As the postresuscitation care bundle is known to be, the present paper focuses on the role of SFI played on the postresuscitation care bundle.